Risk factors of toxoplasmosis in goat and sheep that influence in human infection - Fatmawati, Mira; Padaga, Masdiana C; Mayashinta, Dearikha Karina; Aini, Fidi Nur (Faculty of Animal Science, Universitas Brawijaya, 2021)
Toxoplasmosis is a zoonosis that is transmitted from animals to humans. The definitive landlady of toxoplasmosis is a cat. However, goats can be infected by this disease. One third of the world's humans are estimated to be infected with toxoplasmosis. The purpose of this study was to determine the factors that influence the incidence of toxoplasmosis in humans and animals. The research method is by serological testing of toxoplasmosis in humans using ELISA and serological testing of toxoplasmosis in goats and sheep using ToMAT. The results showed that the prevalence of toxoplasmosis in humans was 15.1% while in goats it was 61.1% and in sheep it was 58.9%. Risk factors that influence the incidence of toxoplasmosis are maintenance management factors such as feeding from grass that take it from fields, provision of drinking water collected, procedures for providing cages, and also cat litter available. While health management factors that become risk factors are separated of sick animals. Potential human transmission through knowledge, attitudes and practices of farmers related to the control of toxoplasmosis. The conclusion of this study is the need for socialization to farmers to improve knowledge, attitudes and practices of farmers related to maintenance management and health enforcement factors that are a risk of transmitting toxoplasmosis, enclosure sanitation and maintenance management.